7.2: Invited Paper: High Efficiency Internal Extraction Substrate for OLED Lighting. (4th October 2019) - Lu, Hong; Jou, Jwo-huei; Xu, Ya-Chen; Huang, Gang-Yi; Gong, Li-Na; Lo, Cheng-chieh; Chen, Jing-Hsiu
Abstract : FOL's OCEANCLEAR series high‐efficiency IES (internal extraction structure) substrates have actually been applied to Gen‐II line for mass production. White OLED panels made on basis of the IES substrates show a power efficacy of around 95lm/W at 1000cd/m 2 . A candlelight‐style desk lamp used IES panel shows a color temperature of around 1700k, a power efficacy of 60lm/W at 1000cd/m 2 . Mass production of IES substrates where achieved by two key technologies: one‐layer coating method and heat‐resisting carrier resin formation.